Increase collaboration willingness through trust building in university-industry collaboration: a higher education institution-level evidence from China - Hu, Shi; Nadeem, Muhammad Aamir; Wang, Ying (Frontiers in Education, 2025)
IntroductionSuccessful university-industry collaboration (UIC) largely depends on the close relationship and effective engagement between higher education institutions (HEIs) and industrial practitioners. The purpose of this study is to analyze the industrial enterprise's willingness to collaborate with HEIs in the UIC regarding the development of degree curricula.MethodsData for this study were collected from HEIs using a questionnaire administered with a two-week time lag, yielding 521 valid responses, which were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Results and discussionIt was confirmed that both ethical and servant leadership in HEIs affect industrial practitioners' trust level in the UIC. Additionally, it was discovered that industrial practitioners' trust in HEIs could foster their willingness to collaborate with HEIs in the UIC. Leaders' self-mindfulness training for ethical or servant leadership implementations in HEIs strengthens the significant associations between these two leadership styles and increased trust among industrial practitioners at the UIC. Finally, the theoretical and practical implications of this research were presented.